AB1076 Course of Physical Functioning and Pain in Osteoarthritis of the Knee or Hip: A Systematic Review. (10th June 2014) - De Rooij, M.; van der Leeden, M.; Häkkinen, A.; Lems, W.F.; Roorda, L.D.; Veenhof, C.; de Vet, H.C.; Dekker, J.
Abstract : Background: The natural course of physical functioning in knee and/or hipOA is highly variable; some patients remain stable, while others improve or worsen. Knowledge on prognostic risk factors related to physical functioning are used to adapt interventions. Objectives: (1) To systematically summarize the literature from March 2005 to January 2013 on the course of physical functioning and pain in patients with OA of the knee or hip and (2) to provide an overview of prognostic factors of physical functioning and future pain for these patients. Methods: A search was conducted in PubMed, CINAHL, Embase and Psych-INFO in January 2013. Eligible studies were prospective cohort studies that included participants with knee or hip OA diagnosed with radiographically and/or clinically diagnosed knee or hip OA, or participants with knee or hip pain who were likely to have OA. Outcome measures were measurements that evaluated physical functioning and pain. The included articles were assessed for bias and the results were summarized according to best evidence synthesis. Results: Of the 9068 studies that were found, 27 articles were included. In patients with knee OA, the average course of physical functioning varied between studies (inconsistent evidence). The same was found for the average course of knee pain in studies with a follow up period shorter than three years. In addition, in patients with hip OA the average course of physical functioning in studies with a follow up period shorter than three years was found to be stable (strong evidence). Because only one study examined the course of physical functioning over a period longer than three years, weak evidence was found for a stable course over 5 years. With regard to prognostic factors, in patients with knee OA strong evidence was found for various prognostic factors for future deterioration in physical functioning i.e. older age, a low to middle education level, higher body mass index, high morbidity count, use of pain medication, greater difficulties with physical functioning at baseline, lower knee extension strength, higher pain intensity, patella-femoral joint compression, lower walking ability, poor mental health and a low vitality. With regard to predictors for future knee pain, a longer symptom duration, bilateral knee symptoms and a higher level of pain at baseline were found to predict future pain in patients with knee OA (strong evidence). In hip OA strong evidence was found that a high morbidity count and a low vitality increase the likelihood of deterioration of physical functioning. No publications were found on prognostic factors for future pain. Conclusions: The average course of physical functioning and pain in patients with knee OA was found to be variable between studies. In hip OA, the long-term course of physical functioning was found to be stable. In comparison to a previous review stronger evidence was found for a number of variables to be prognostic factors of physical functioning and pain, including demographic factors, clinical factors, knee characteristics and psychosocial factors. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2830